Retroperitoneal cystic metastasis from cervical cancer: a rare case report - V., Shruthikamal; S., Reshma; A., Akmal (International Surgery Journal, 2017)
Cervical cancer accounts for 5% of all cases of cancer diagnosed worldwide. Cervical carcinoma commonly spreads via the lymphatics, with metastases first occurring in the pelvic lymph nodes, and then sequentially spreading to the paraortic nodes. Retroperitoneal cystic metastases originating from cervical cancer is extremely rare. In patients undergoing chemoradiation, isolated failure in the lymph nodes is uncommon and is more commonly associated with failure to control the primary tumor. Study report a case of 62 years old woman with retroperitoneal cystic metastasis from cervical cancer managed with cystojejunostomy along with Roux en y reconstruction and chemotherapy.